Feminist Methodologies Experiments, Collaborations and Reflections - Harcourt, Wendy; van den Berg, Karijn; Dupuis, Constance; Gaybor, Jacqueline (Gender, Development and Social Change, 2022)
This open access book gives insights into feminist methodologies in theory and practice. By foregrounding the experiential and embodied nature of doing feminist research, this book offers valuable tools for feminist research as a continuous praxis. Emerging from a rich collective learning process, the collection offers in-depth reflections on how feminists shape research questions, understand positionality, share research results beyond academe and produce feminist intersectional knowledges. This book reveals how the authors navigate theory and practice, candidly exploring the difficulty of producing knowledge on the edge of academia and activism. From different points of view, places and disciplinary positions, artistic and creative experiments and collaborations, the book provides a multi-layered analysis. This book will be a valuable resource and asset to early career researchers and interdisciplinary feminist students who can learn more about the doing of feminist research from realistic, accessible, and practical methodological tools and knowledge.